Canadian Communists, Revolutionary Unionism, and the “Third Period”: The Workers’ Unity League, 1929-1935 - Manley, John (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1994)
AbstractIn compliance with the Third Period "line" of the Communist International (Comintern), the Communist Party of Canada (CPC) launched The Workers' Unity League (WUL) as a centre of "revolutionary" or "red" unionism in December 1929. Until it was "liquidated" during the winter of 1935-6, the WUL had a significance in Canada's Depression labour struggles far outweighing its maximum membership of between 30,000 and 40,000; a significance, moreover, that has yet to be fully acknowledged or analysed. This article seeks to look beyond the conventional view that presents the CPC as a Comintern cipher and the WUL (when it is considered at all) as a "sectarian", "adventurist", "ultra-left" organisation with no real interest in building stable labour unions. While there is no doubt that the two most crucial decisions concerning the WUL — to create it and to liquidate it — were taken in Moscow, neither the Comintern nor the CPC leadership in Toronto was in a position to supervise the implementation of the Third Period line on the ground. Within the broad parameters of the line, local organisers tended to operate as "good trade unionists" rather than "good bolsheviks", using every available opportunity to modify and adapt tactics to local realities. They used their room for manoeuvre to considerable effect, especially during the economic and political upturn of 1933-34, when the WUL led a majority of all strikes and established union bases in a host of hitherto unorganised or weakly organised industries. At the height of its power, however, the WUL knew that it had barely dented the essential mass production industries — auto, steel, rubber, farm machinery. This fact, coupled with the experience of defeat in several key strikes,forced the party to reconsider the WUL's future. Whether the WUL could have survived as part of a national union centre remains open to question. Indisputably, the Comintern terminated that option in 1935.